Il est seigneur sur les nations: étude structurelle du psaume 110 - Auffret, Pierre (Biblische Notizen, 2004)
Making profitably a most interesting proposal (of 1994) by Girard, on the literary structure of Ps 110, the author of this item takes benefit of it to adjust the one he himself had risked in 1982. This new course makes it possible to release the four units into 1-2, 3, 4 and 5-7, each one being in itself structured. Then the relationship can be discovered between the extreme units, as well the parallel between 1-2 + 3 and 4 + 5-7. All these sets of relationships offer an invaluable point of support to the interpretation of this difficult psalm.